Total Laparoscopic Conservative Surgery for an Intramural Ectopic Pregnancy - Nabeshima, Hiroshi (Hindawi Publishing Corporation, 2010)
A 38-year-old woman, gravida 3, para 1 with a history of a left salpingectomy for an ectopic pregnancy was admitted for treatment of a presumed ectopic pregnancy. Transvaginal sonography revealed an ill-defined gestational sac and fetal heart beat within the fundal myometrium adjacent to the left cornua. Laparoscopy was performed for a suspected left cornual pregnancy or intramural pregnancy. A cystic mass 3 cm in diameter was visible within the fundal myometrium. Total laparoscopic removal of the gestational sac was performed, and the uterus was preserved. Pathologic evaluation of the excised mass demonstrated chorionic villi involving the myometrium. In the literature, only one other case describing the laparoscopic removal of an intramural pregnancy has been reported. However, in the prior report, the patient still required hysterectomy after conservative surgery. Therefore, this is the first report of the successful treatment of an intramural pregnancy exclusively with laparoscopy.